Analisis Tax Compliance Behavior Pendekatan Theory Of Planned Behavior - Manullang, Mega Utami; Khairudin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Tax administration in Indonesia is developing progressively with changes in organizational systems, work facilities and infrastructure, regulations and tax administration apparatus that have donated to state revenues. The research is aimed at demonstrating in reality the existence of tax compliance behavior. Based on the theory of planned behavior. In this study, four independent variables were tested, namely taxpayer behavior, subjective procedures, tax payer behavior control, and tax payer moral obligations. The population in this study is the Bandar Lampung Pratama Tax Service workplace with 100 respondents in the survey. Multiple linear regression is used as the method of analysis. There will be research showing that behavior must be taxed and moral obligation must be taxed is influenced by the intention to comply with the tax. Meanwhile, subjective norms and attitude control for tax compliance have no effect on tax compliance behavioral intentions. Keywords: Attitude of the Taxpayer, Subjective Norms, Taxpayer Behavior Control, Taxpayer's Moral Obligations, on Intentions of Tax Compliance Behavior.